PENINGKATAN AKSES PANGAN BAGI MASYARAKAT PERKOTAAN MELALUI PELATIHAN VERTICAL FARMING DAN PERTANIAN ORGANIK [IMPROVING FOOD ACCESS FOR A MARGINAL URBAN COMMUNITY THROUGH VERTICAL AND ORGANIC FARMING TRAINING] - Firman Zulpikar; Abel Gandhy; Warsono El Kiyat (Universitas Pelita Harapan, 2020)
Housing and business centers are growing rapidly in the urban area. This causes agricultural land and other green lands increasingly narrow due to land conversion. One area affected by land conversion is Lengkong Kulon Village, Tangerang Regency, where most of the agricultural land has been turned into a residential area and business center. This condition has an impact on food availability which is getting lower and environmental quality is declining. To overcome these problems, Surya University, supported by the Ministry of Research, Technology, and Higher Education (Kemenristekdikti), organized community service activities by pioneering sustainable green villages and adequate nutrition through vertical farming. This program was implemented by the workshop and participatory community. The number of participants involved in this activity was more than 25 people from youth groups concerned about the environment, PKK members, and university students. This activity consisted of three stages: Community awareness building, Vertical and organic farming training, and Providing vertical farming equipment assistance packages. The result of this community service showed that participants knowledge about organic farming and vertical farming increased from 26% to 86% and from 11% to 72%, respectively. In addition, the level of community skills to apply organic farming systems also increased from 15% to 80%, and for vertical farming increased from 7% to 60%. This activity is expected to improve environmental conditions as well as food access for target communities through consumption of sufficients vegetables and fruits grown using the vertical farming system. Bahasa Indonesia Abstrak: Abstrak Pesatnya pembangunan komplek perumahan dan pusat bisnis di perkotaan telah menyebabkan semakin sempitnya lahan pertanian dan lahan hijau lainnya akibat alih fungsi lahan. Salah satu wilayah yang terkena dampak alih fungsi lahan adalah Kampung Lengkong Kulon, Desa Lengkong Kulon, Kabupaten Tangerang di mana sebagian besar lahan pertaniannya telah berubah menjadi kawasan perumahan dan pusat bisnis. Kondisi ini telah berimplikasi pada ketersediaan pangan yang semakin rendah serta kualitas lingkungan yang menurun. Untuk mengatasi permasalahan tersebut, Universitas Surya yang didukung oleh Kementristekdikti menyelenggarakan kegiatan pengabdian masyarakat dengan tema rintisan kampung hijau lestari dan cukup gizi melalui vertical farming. Program ini dilaksanakan menggunakan model workshop dan participatory community. Jumlah peserta yang terlibat dalam kegiatan ini yaitu lebih dari 25 orang, yang berasal dari kelompok pemuda peduli lingkungan, ibu-ibu PKK, anggota posyandu, serta kelompok mahasiswa. Tahapan kegiatan ini meliputi pembangunan kesadaran masyarakat (community awareness), pelatihan vertical farming dan pertanian organik, serta pemberian paket bantuan peralatan vertical farming. Hasil evaluasi pelatihan menunjukkan bahwa terjadi peningkatan pengetahuan masyarakat tentang pertanian organik dari semula hanya 26% menjadi 86%, sedangkan untuk vertical farming dari semula 11% meningkat menjadi 72%. Tingkat keterampilan masyarakat untuk menerapkan sistem pertanian organik juga meningkat dari semula hanya 15% menjadi 80%, sementara untuk untuk vertical farming dari semula 7% meningkat menjadi 60%. Kegiatan ini diharapkan dapat memperbaiki kondisi lingkungan serta adanya peningkatan akses pangan bagi masyarakat sasaran melalui konsumsi sayuran dan buahbuahan yang cukup, yang ditanam menggunakan sistem vertical farming.